2008
DOI: 10.1590/s1516-35982008000700007
|View full text |Cite
|
Sign up to set email alerts
|

Análise de trilha em caracteres produtivos de Pennisetum sob corte em Itambé, Pernambuco

Abstract: RESUMO -Objetivou-se obter estimativas de coeficientes de correlação genética e avaliar os desdobramentos das correlações em efeitos diretos e indiretos (análise de trilha) das variáveis independentes explicativas sobre a produção de matéria seca (variável dependente principal) em cinco clones de capim-elefante. Foram realizados cinco cortes a cada 60 dias nas condições edafoclimáticas da Zona da Mata de Pernambuco. Cada parcela experimental apresentou 24 m 2 , com 2 m 2 de área útil. Houve alta correlação ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
9
2
3
Order By: Relevance
“…However, in this study, this parameter had little importance for selection, showing reduced heritability and associations that compromise TDM and LDM. This trend was also observed by Silva et al (2008) for different species of the genus Pennisetum. These authors argued that the water stress occurred in certain cuts increased the tiller density, but without leaf expansion.…”
Section: Trait Meansupporting
confidence: 73%
See 4 more Smart Citations
“…However, in this study, this parameter had little importance for selection, showing reduced heritability and associations that compromise TDM and LDM. This trend was also observed by Silva et al (2008) for different species of the genus Pennisetum. These authors argued that the water stress occurred in certain cuts increased the tiller density, but without leaf expansion.…”
Section: Trait Meansupporting
confidence: 73%
“…Basso et al (2009) also detected strong associations between TDM and LDM of Paspalum in the different study locations. Several authors reported that tiller number influences the total dry matter production (Alexandrino et al, 2005;Silva et al, 2008). However, in this study, this parameter had little importance for selection, showing reduced heritability and associations that compromise TDM and LDM.…”
Section: Trait Meancontrasting
confidence: 56%
See 3 more Smart Citations